Advanced Water Management in PEFCs: Diffusion Layers with Patterned Wettability I. Synthetic Routes, Wettability Tuning and Thermal Stability. Issue 8 (1st January 2016) - Forner-Cuenca, Antoni; Manzi-Orezzoli, Victoria; Biesdorf, Johannes; Kazzi, Mario El; Streich, Daniel; Gubler, Lorenz; Schmidt, Thomas J.; Boillat, Pierre
Abstract : A novel type of fuel cell gas diffusion layer with patterned wettability is herein reported. The production of hydrophilic patterns by radiation grafting depends on two main steps: electron beam activation and polymerization reaction. In this first part of the series, we are giving extensive details about the synthetic routes for modifying porous media's wettability. Two monomers (acrylic acid and N-vinylformamide) were used for the hydrophilization of the fluoropolymer and a parametric study was performed. Finally, a preliminary thermal degradation study was carried out. We found conditions to produce hydrophilic gas diffusion layers with short reaction times (about 10 minutes) and proved that the synthetic method is suitable for creating local modifications. For hydrophilic surfaces, the coating load significantly impacts wetting dynamics.